2020
DOI: 10.1016/j.virusres.2020.198070
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Review on latest available drugs and therapies against SARS-CoV-2. Coagulation and inflammation cross-talking

Abstract: SARS-CoV-2 is the agent responsible for COVID-19. The infection can be dived into three phases: mild infection, the pulmonary phase and the inflammatory phase. Treatment options for the pulmonary phase include: Hydroxychloroquine, Remdesivir, Lopinavir/Ritonavir. The inflammatory phase includes therapeutic options like Tocilizumab, Anakinra, Baricitinib, Eculizumab, Emapalumab and Heparin. Human clinical trials are starting to show some results, in some cases like that of Remdesivir and corticosteroids these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 133 publications
(215 reference statements)
2
121
1
1
Order By: Relevance
“…As mentioned above, excessive IL-6 levels are highly correlated with the lethal complications of COVID-19 patients [16,64,65]. Notably, a previous report showed that inhibition of the NF-κB pathway in animals infected with SARS-CoV decreases mortality and IL-6 levels [66].…”
Section: Possible Therapeutics For Covid-19mentioning
confidence: 90%
“…As mentioned above, excessive IL-6 levels are highly correlated with the lethal complications of COVID-19 patients [16,64,65]. Notably, a previous report showed that inhibition of the NF-κB pathway in animals infected with SARS-CoV decreases mortality and IL-6 levels [66].…”
Section: Possible Therapeutics For Covid-19mentioning
confidence: 90%
“…Recent findings are optimistic, but data validation by robust scientific evidence has been hampered by the small sample size in most case reports and studies on the use of mAbs blocking other immune mediators, such as IL-1b, GM-CSF, and complement protein C5 (238,(248)(249)(250). However, seeking to verify the effectiveness of using mAbs blocking inflammatory mediators, dozens of clinical trials are currently underway.…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…The complex inflammatory and coagulation impact of COVID-19 must be understood in detail in order to mount precise treatment and patient stratification. 99 Complete biomarkers profiling using comprehensive molecular tools could be important to predict patients who are most likely to recover or progress to withstand cytokine storms. However, there is opportunity for global cooperation to advance scientific understanding of drug discovery and vaccine development.…”
Section: Resultsmentioning
confidence: 99%